PTH-106 Survival outcomes following hepatectomy for stage iv colorectal liver metastases: a comparison of liver- versus colon-first approach. (22nd June 2015) - Yip, V
Abstract : Introduction: Liver-first approach compared to colon-first staged approach has been advocated for stage IV colorectal liver metastases (CRLM), but there is limited survival data to compare between these strategies. Our aim was to compare long term survival outcomes for liver- versus colon-first approach for stage IV CRLM. Method: Between 2008 and 2013, patients with completed liver and colon resections for stage IV CRLM were included in this study. Patients with extrahepatic disease, synchronous resections and emergency colectomies were excluded. Patients in liver- (A) and colon- (B) first were stratified and compared using the Fong's Clinical Risk Score (CRS). Results: N=172 patients presented with stage IV colorectal cancer during the study period. N=25 had extrahepatic metastases, and were excluded. A further n = 88 patients, who underwent liver or colon resection were excluded as a result of disease progression (n = 11 liver n = 77 colon). N=59 (40%) had completed both liver and colonic resections, and comprised the study group (Group A: N=31; Group B: N=29). All patients had undergone neoadjuvant chemotherapy prior to resection. There was no difference in terms of age (p = 0.213), gender (p = 0.424), number (p = 0.839) and size (p = 0.725) of liver lesions in both groups. Fong's CRS (1–5) was not significantly different for both treatment groups (p = 0.450). There was no difference in the overall survival (OS) (p = 0.846) and disease-free survival (DFS) (p = 0.675) between Group A and Group B. One-, 3- and 5-year OS for Group A versus Group B were 94% vs. 97%, 75% vs. 76% and 46% vs. 54%; and the DFS was 76% vs. 78%, 41% vs. 28% and 41% vs. 22% respectively. Conclusion: The overall survival for liver-first approach is comparable to classic staged approach for stage IV colorectal cancer. Although not statistically significant, liver-first approach appears to provide a better disease-free survival at 3- and 5-years. Disclosure of interest: None Declared.